A prática dos professores de português e a relação com a formação de produtores de texto escrito no ensino médio - BARCESSAT, Felipe Luiz Ribeiro (UNIFAP – Universidade Federal do Amapá, 2022)
This qualitative and observational research aims to analyze the conditions of production of written texts, in the third year, of the secondary level of two public schools of the state network in the municipality of Macapá, Amapá. During two months, in 2008, we observed situations of work with the textual production, carried out by the teachers, aiming to collect texts, from the students, to analyze the production conditions. During this period we were able to collect 14 texts, and carry out interviews with the teachers, dealing with the work with writing. For the analysis of texts, teachers' responses and observations, we used as a parameter the production conditions proposed by Geraldi, Antunes and others. We adopted, as a theoretical basis, the interactionist perspective of language, seeking in the studies of Bakhtin and Vygostski, the main source to guide studies and reflections. Based on this view, it was found that teachers still have a traditional conception of language, which incisively reflects on the teaching-learning of the production of written texts in the classroom. The production conditions identified in the students' texts are artificial, typical of school writing activities. Which portrays a traditional conception of language, which does not provide the development of writing as a social practice. Finally, we show the results obtained with the intervention of the researchers in one of the field schools; and we discussed the current teaching-learning situation of the production of written texts, launching reflections on a teaching concept that allows the student to interact, through written language, in situations of effective use of the language.